The importance of the University Restaurant in maintaining students’ food security: An integrative systematic literature review (Research, Society and Development, 2026)
Food security is fundamental to guaranteeing health and access to food. To ensure that higher education students have access to quality food that enables their continued enrollment in public institutions and aids in their physical and mental development, the Federal Government establishes University Restaurants (RUs) through the National Student Assistance Policy (PNAES). This is an exploratory and descriptive study aiming to analyze the effectiveness of RUs in preventing food insecurity in public universities. The selection process used criteria of thematic relevance and methodological robustness, prioritizing empirical studies that offered quantitative and qualitative data on access to food in the university context. The results showed the selection of 10 empirical studies, published between 2013 and 2025, which indicate a positive correlation between access to RUs and academic performance, revealing their role in guaranteeing social security. Based on the studies analyzed, it was possible to observe the crucial role that university restaurants play in combating food insecurity among students, through affordable, quality meals, optimizing students' time and enabling greater participation in academic activities, thus acting as a protective factor against dropout. Therefore, it is clear that these restaurants are an essential tool for promoting food security among students.